2013
DOI: 10.1002/chem.201301406
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Enhancement of Electrocatalytic Oxygen‐Reduction and Hydrogen‐Evolution Performance of MoS2 Particles

Abstract: MoS2 particles with different size distributions were prepared by simple ultrasonication of bulk MoS2 followed by gradient centrifugation. Relative to the inert microscale MoS2, nanoscale MoS2 showed significantly improved catalytic activity toward the oxygen-reduction reaction (ORR) and hydrogen-evolution reaction (HER). The decrease in particle size was accompanied by an increase in catalytic activity. Particles with a size of around 2 nm exhibited the best dual ORR and HER performance with a four-electron O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
203
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(212 citation statements)
references
References 77 publications
9
203
0
Order By: Relevance
“…Such layered assemblies offer a large number of edges (inset of Fig. 1b), which are believed to be highly electrocatalytically active sites in electrochemical reactions 17,23 . To further detail the atomic arrangement, scanning transmission electron microscopy (STEM) analysis was performed on several mechanically exfoliated, mono-and multi-layer-thick sheets of MoS 2 flakes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such layered assemblies offer a large number of edges (inset of Fig. 1b), which are believed to be highly electrocatalytically active sites in electrochemical reactions 17,23 . To further detail the atomic arrangement, scanning transmission electron microscopy (STEM) analysis was performed on several mechanically exfoliated, mono-and multi-layer-thick sheets of MoS 2 flakes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the CO 2 reduction current density for MoS 2 is also significantly higher ARTICLE than the maximum current density (B8.0 mA cm À 2 ) achieved when Ag NPs were used in the dynamic electrochemical flow cell using a similar electrolyte solution 13 . For all the cases, the current densities were normalized against the geometrical surface area 9,10,[16][17][25][26] . Surprisingly, the MoS 2 catalyst also shows a high current density (50 mA cm À 2 ) in an Ar-saturated electrolyte, where only H 2 was detected as the major product (Supplementary Note 1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of the ultrathin MoS 2 monolayer, the electro-catalytic property has attracted great attention 2629 . It was reported that with the decrease of monolayer size, MoS 2 reveals favorable performance in ORR and hydrogen evolution reaction (HER) 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The observed Tafel slope is among the best-reported slope for MoS2. For example, Tafel slopes of 87, 82 and 77 mV/decade were reported for defect-free MoS2 nanosheets, nanosized bulk MoS2 and MoS2 nanoparticles, respectively [42][43][44]. Lithium intercalated MoS2 showed a Tafel slope of 62 mV/decade [22].…”
Section: Introductionmentioning
confidence: 99%